Implementasi Model Problem Based Learning pada Pelajaran Dasar-Dasar Ketenagalistrikan Berbantuan ChatGPT untuk Meningkatkan Hasil Belajar Siswa SMK Negeri 5 Padang - Deska Harnando Edo; Usmeldi Usmeldi (Journal of Electrical Vocational Education, 2025)
This study aims to examine the effect of the implementation of Problem Based Learning assisted by ChatGPT on student learning outcomes in the subject of Basics of Electricity at SMK Negeri 5 Padang. The research method used a pre-experimental design with a one-group pretest-posttest design. The research subjects were students of class X TITL 3 SMK Negeri 5 Padang in the 2024/2025 academic year. Data were collected through an initial test (pretest) and a final test (posttest). The results showed that there was an increase in learning outcomes with moderate criteria, indicated by a normalized gain score of 0.39. A total of 90% of students achieved learning completeness (KKTP), while 10% had not yet completed it. These findings prove that the Problem Based Learning Model assisted by ChatGPT can improve the learning outcomes of class X TITL 3 SMK Negeri 5 Padang students. This study contributes to the development of innovative technology-based learning methods for engineering subjects.